Evaluating the Knowledge of Moroccan Patients Regarding their Oral Anticoagulant Treatment Admitted in Cardiology and Cardiovascular Surgery Units - Esso Eric Valery Latt; Youssef Moutaouakkil; Badreddine Moukafih; Yahia Cherrah; Jamal Lamsaouri; Yassir Bousliman (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background. Vitamin K antagonists (VKAs), the most commonly used anticoagulants worldwide. Our aim was to assessing the moroccan patients’ knowledge regarding their VKA treatment after their hospital stay in Cardiology and Cardiovascular Surgery units before being discharged home.Methods. One hundred and twenty-three patients were enrolled in this prospective, monocenter study. Their level of knowledge was assessed by a semi-structured interview between the pharmacist and the patients.Results. 75,61% of patients were able to give the name of the drug they were taking, 76,42 % could explain its effect and finally, 79,67% of patient knew their INR target values. 19,51 % of patients were able to describe the symptoms in case of overdose and what to do in that case. 47,15 % of patients were aware of food interactions and 56,09 % of self-medication risks. Conclusion. Our study, as in previous studies among Patients with chronic diseases, identified some gaps in knowledge. These findings indicate the need for better education of patients regarding their VKA treatment.